Writing strategies of good writers of expository composition in upper secondary school - Renuka Thankak Krishnah. (2008)
Writing is an essential component of the GCE "O" Level Examination. The secondary school students' ability to produce texts that are coherent, organised and following the convention of the genre are very important in determining if the written text is successful or not. This is especially evident in the case of the expository discourse. The secondary school students who move on to the polytechnic or the pre-university to continue their education, will need to know how to write expository texts as they will have to write assignments of the expository genre in these institutions. Those students who lack the strategies of communicating the information in the appropriate manner will find themselves at a disadvantage and will not be able to put forward a convincing argument in relation to the given task.